ANALISIS PERAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS III PADA PEMBELAJARAN JARAK JAUH - Yasmin Mutmainnah, - (2021)
Learning activities have the meaning of continuous learning to determine student learning outcomes. If teachers and students in schools reciprocate in learning activities, learning goals will be achieved. In general, learning activities are carried out in a room with several groups of people. Classroom teaching activities are carried out by listening to teachers, discussing together and solving problems together. Since the Covid-19 pandemic, learning has been implemented using distance learning methods. According to the Ministry of Education and Culture (Kemendikbudd) No. 4 of 2020, this is related to policies related to the spread of coronavirus infection and emergency education. Submissive teacher. This study was conducted to understand the difficulties parents face in the distance learning process and to understand the role of parents who are motivated to learn during the level III of the research site SDN 10 Nagri Kaler Purwakarta. The method used to find the results of this study is descriptive and qualitative, because the researcher will derive the phenomenon that occurred in the research object. The role of parents will affect the learning motivation of parents. The role of parents is to replace the teacher's role in the school, provide learning facilities, provide motivation and enthusiasm, and mobilize their enthusiasm according to their children's interests and talents.